UJI AKTIVITAS ANTIBAKTERI EKSTRAK METANOL MIKROALGA Chlorella sp. PADA FASE STASIONER HASIL KULTIVASI DALAM MEDIUM EKSTRAK TAUGE (MET) - khamidah, Umi; Fasya, Ahmad Ghanaim; Romaidi, Romaidi (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2014)
Chlorella sp. is one of microalgae Chlorophyta that containing kinds of important compound such as flavonoid, tanin, phenolic compound, terpenoid, chlorophyll and karotenoid. The purpose of this research are to know antibacterial activity from methanol extract of microalgae Chlorella sp. at stationary phase and to know contains of active compound group in extract of microalgae Chlorella sp. Chlorella sp. was cultivated in Tauge Extract Medium (TEM) 4 % and harvesting of stationary phase. Extraction microalgae Chlorella sp. was performed by maceration with methanol solvent. Methanol extract from stationary phase were tested antibacterial activity with concentration variation 5 %, 10 %, 15 %, 20 %, and 25 % used diffusion method toward E. coli and S. aureus bacterium. Identification of active compound was estimated by reagent tested on qualitative scale include alkaloid, falvonoid, steroid, triterpenoid, and tanin. The result showed that methanol extract of Chlorella sp. in stationary phase in concentration %, 10 %, 15 %, 20 %, and 25 % with inhibition zone as follows 1,0 mm, 3,7 mm, 6,9 mm, 16,5 mm and 12,1 mm toward E. coli bacterium and 2,2 mm, 4,9 mm, 3,0 mm, 7,4 mm, and 13,1 mm toward S. aureus bacterium. The results of the identification of the compound methanol extract of microalgae Chlorella sp.contains a steroid and tanin compound class